3,4-dihydroxytoluene, a metabolite of rutin, suppresses the progression of nonalcoholic fatty liver disease in mice by inhibiting p300 histone acetyltransferase activity - Lee Jangho; Song Ji-Hye; Chung Min-Yu; Lee Jin-Hyuk; Nam Tae-Gyu; Park Jae Ho; Hwang Jin-Taek; Choi Hyo-Kyoung (Acta Pharmacologica Sinica, 2021)
3,3′,4′,5,7-Pentahydroxyflavone-3-rhamnoglucoside (rutin) is a flavonoid with a wide range of pharmacological activities. Dietary rutin is hardly absorbed because the microflora in the large intestine metabolize rutin into a variety of compounds including quercetin and phenol derivatives such as 3,4-dihydroxyphenolacetic acid (DHPAA), 3,4-dihydroxytoluene (DHT), 3,4- hydroxyphenylacetic acid (HPAA) and homovanillic acid (HVA). We examined the potential of rutin and its metabolites as novel histone acetyltransferase (HAT) inhibitors. DHPAA, HPAA and DHT at the concentration of 25 μM significantly inhibited in vitro HAT activity with DHT having the strongest inhibitory activity. Furthermore, DHT was shown to be a highly efficient inhibitor of p300 HAT activity, which corresponded with its high degree of inhibition on intracellular lipid accumulation in HepG2 cells. Docking simulation revealed that DHT was bound to the p300 catalytic pocket, bromodomain. Drug affinity responsive target stability (DARTS) analysis further supported the possibility of direct binding between DHT and p300. In HepG2 cells, DHT concentration- dependently abrogated p300-histone binding and induced hypoacetylation of histone subunits H3K9, H3K36, H4K8 and H4K16, eventually leading to the downregulation of lipogenesis-related genes and attenuating lipid accumulation. In ob/ob mice, administration of DHT (10, 20 mg/kg, iv, every other day for 6 weeks) dose-dependently improved the NAFLD pathogenic features including body weight, liver mass, fat mass, lipid accumulation in the liver, and biochemical blood parameters, accompanied by the decreased mRNA expression of lipogenic genes in the liver. Our results demonstrate that DHT, a novel p300 histone acetyltransferase inhibitor, may be a potential preventive or therapeutic agent for NAFLD.